3D Printing: Complex‐Shaped Cellulose Composites Made by Wet Densification of 3D Printed Scaffolds (Adv. Funct. Mater. 4/2020). (24th January 2020) - Hausmann, Michael K.; Siqueira, Gilberto; Libanori, Rafael; Kokkinis, Dimitri; Neels, Antonia; Zimmermann, Tanja; Studart, André R.
Abstract : Cellulose, extracted from wood, is a renewable and biodegradable material that can find potential applications in the biomedical, electronic, and food industries. In article number 1904127, Gilberto Siqueira, Rafael Libanori, and André R. Studart show that cellulose nanofibrils or cellulose nanocrystals can be aligned at the microscale and shaped into unique geometries at the macroscale during the 3D printing process to result in composite objects that resemble the exquisite hierarchical structure of wood.